2016
DOI: 10.1080/19420862.2016.1160192
|View full text |Cite
|
Sign up to set email alerts
|

Development of purification processes for fully human bispecific antibodies based upon modification of protein A binding avidity

Abstract: There is strong interest in the design of bispecific monoclonal antibodies (bsAbs) that can simultaneously bind 2 distinct targets or epitopes to achieve novel mechanisms of action and efficacy. Multiple bispecific formats have been proposed and are currently under development. Regeneron's bispecific technology is based upon a standard fully human IgG antibody in order to minimize immunogenicity and improve the pharmacokinetic profile. A single common light chain and 2 distinct heavy chains combine to form the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 36 publications
2
75
1
1
Order By: Relevance
“…This explanation is consistent with the fact that IgG 1 , IgG 2 , and IgG 4 species contain two functional ProA binding sites on the Fc region of the antibody (Moks et al, 1986;Sj€ oquist et al, 1972). In fact, Tustian et al (2016) recently demonstrated that removing one of these Fc binding sites via protein engineering resulted in higher elution pHs, and thus, lower binding strength, from multiple ProA resins due to ligand avidity.…”
Section: Clsm Adsorption Experimentssupporting
confidence: 82%
See 1 more Smart Citation
“…This explanation is consistent with the fact that IgG 1 , IgG 2 , and IgG 4 species contain two functional ProA binding sites on the Fc region of the antibody (Moks et al, 1986;Sj€ oquist et al, 1972). In fact, Tustian et al (2016) recently demonstrated that removing one of these Fc binding sites via protein engineering resulted in higher elution pHs, and thus, lower binding strength, from multiple ProA resins due to ligand avidity.…”
Section: Clsm Adsorption Experimentssupporting
confidence: 82%
“…5c and 6c. In fact, Tustian et al (2016) recently demonstrated that removing one of these Fc binding sites via protein engineering resulted in higher elution pHs, and thus, lower binding strength, from multiple ProA resins due to ligand avidity. Since the extent of desorption of the mAb was similar from MabSelect and MabSelect SuRe at 4 h (57 AE 7%), these results suggest that species of equivalent or near equivalent elution pH were also capable of displacing each other on the resin.…”
Section: Clsm Adsorption Experimentsmentioning
confidence: 99%
“…For any 2 antibodies containing a common LC, bsAb purification can be expedited by incorporating mutations that ablate protein A binding into one of the parental HCs. 267 After coexpression of the 2 HCs and a common LC, bsAbs can be purified from the mixture using protein A resin combined with incremental decreases in buffer pH. The species containing 2 mutated HCs flows through the column, while the heterodimer elutes at intermediate pH and the wild-type HC homodimer elutes only at low pH because of strong protein A avidity.…”
Section: Asymmetric Igg-like Frameworkmentioning
confidence: 99%
“…Two different variations of each antibody were cloned to contain either the F405L or K409R mutation to promote cFAE [33]. Furthermore, antibodies containing the K409R mutation also contained the H435R and Y436F mutations to ablate protein A binding in one arm of the heterodimer [34]. Antibodies were cloned into a proprietary AstraZeneca mammalian expression vector [35], and transient expression was carried out using suspension-adapted chinese hamster ovary (CHO) cells [36].…”
Section: Transient Expression Of Parental Antibodiesmentioning
confidence: 99%
“…Here, we describe a method for the rapid generation of monovalent bsAbs directly from culture media by combining a single-matched point mutation in the CH3 domain to promote heterodimerization via controlled Fab-arm exchange (cFAE) [33], and by incorporating the H435R and Y436F mutations in the CH3 domain to ablate protein A binding in one arm of the heterodimer to facilitate bsAb purification [34]. Using this approach, highly pure monovalent bsAbs can be rapidly generated and purified directly from combined culture media using standard protein A purification.…”
Section: Introductionmentioning
confidence: 99%